Effect of temperature on larvae growth and physical development of Lampam Jawa, Barbonymus gonionotus (Bleeker, 1849) - Wan Omar, Wan Norshuhada (2016)
Temperature is one of the most important environmental factors that affect the growth and physical development of fish larvae. The temperature in both natural environment and captive breeding are dissimilar. In captive breeding, the temperature is controlled to achieve higher survival. The effect of water temperature on development of Lampam Jawa (Barbonymus gonionotus) larvae was studied. An experiment was designed to observe the effect of temperature changes on the growth and physical development of Barbonymus gonionotus in captive breeding. It was conducted in wet laboratory of UPM, Serdang, Selangor. Broodstock were induced with artificial hormone Ovatide at 0.2ml/kg of male and 0.4ml/kg of female. The larvae were reared in three different temperature periodically at 22 ± 1oC, 27 ± 1oC (room temperature) and 32 ± 1oC. Water temperatures were decreased to 22 ± 1oC, by using Resun CL500 chiller and increased at 32 ± 1oC using Eheim Jager heater. The growth of these larvae were measured daily based on their length and weight. The larvae development was monitored for 28 days during the experiment. Developmental rate increased with increasing temperature. The mean length was significantly bigger (p<0.05) at 8.82± 1.94 mm and the mean weight was at 1.46 g in 32 ± 1oC. Whereas, in 22 ± 1oC, the length was at 6.35 ± 0.52 mm and the mean weight at 0.76 g. In 32 ± 1oC temperature, the fully development of fin can be seen in day 20. Whereas in temperature 22 ± 1oC, the fully development of fin cannot be seen throughout the 28 days experimental period. Results showed that the survival was significantly higher in 32 ± 1oC at 96.31% (p<0.05) and lowest at 36.23% in 22 ± 1oC. In conclusion, the Barbonymus gonionotus has better performance towards high water temperature.